KAJIAN SISTEM INFORMASI MANAJEMEN TERHADAP KESELAMATAN PENERBANGAN PADA AIRNAV JAKARTA - Lut Mafrudoh; Ferizka Wahyuningtias; Chaidir Tasran (Jurnal Manajemen Bisnis Transportasi dan Logistik, 2017)
The purpose of this research is to know how Management Information System related to EFFORT system at AirNav Indonesia JATSC Perum LPPNPI Branch Office, how the safety of flight, how the influence of Management Information System related EFFORT system to safety. This research uses field data (field research) and library (library research). Method of data analysis by using simple linear regression, correlation coefficient analysis, and hypothesis test. The result of analysis and discussion shows a strong relationship between management information system related to EFFORT system with flight safety aimed at correlation coefficient addressed with correlation coefficient r = 0.81 less than 1, and result of hypothesis test show that thitung> ttabel = 1, 85> 1.701 so Ho rejected Ha accepted. This means that there is a significant relationship between management information systems related to the EFFORT system on aviation safety.